2014
DOI: 10.1111/are.12600
|View full text |Cite
|
Sign up to set email alerts
|

Osteological ontogeny and malformations in larval and juvenile golden pompano Trachinotus ovatus (Linnaeus 1758)

Abstract: The osteological ontogeny and the incidence of deformities occurred in vertebral column and caudal complex were studied from 1 day post hatch (DPH) to 31 DPH in Trachinotus ovatus. Results indicate that the development of both caudal complex and vertebral column initiated between 7 DPH and 9 DPH along with the calcification of haemal arches and neural arches, and occurrence of caudal elements. The last element of caudal complex, uroneural, appeared on 18 DPH. A high number of malformations in the vertebral col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 48 publications
1
17
3
Order By: Relevance
“…Skeletal deformities in cultured fish might be caused by various factors, including nutritional imbalances (lysine, vitamin, tryptophan, phospholipid, unsaturated fatty acid) (Cahu, Zambonino Infante, & Takeuchi, ; Lall & Lewis‐McCrea, ), genetic factors (Silva, Cordeiro, Richard, Conceição, & Rodrigues, ) and environmental factors (salinity, photoperiod, dissolved oxygen, water current) (Fjelldal et al., ; Hattori et al., ; Kurokawa et al., ; Okamoto et al., ). In the present study, 34.22% of individuals had skeletal abnormalities, which is higher than that documented for other species, such as D. dentex (Koumoundouros, Divanach, & Kentouri, b), P. fulvidraco (Huang et al., ), T. ovatus (Zheng et al., ) and P. erythrinus (Boglione et al., ). This difference might be due to differences in physical variables, species characteristics, environmental factors and culture conditions.…”
Section: Discussioncontrasting
confidence: 61%
“…Skeletal deformities in cultured fish might be caused by various factors, including nutritional imbalances (lysine, vitamin, tryptophan, phospholipid, unsaturated fatty acid) (Cahu, Zambonino Infante, & Takeuchi, ; Lall & Lewis‐McCrea, ), genetic factors (Silva, Cordeiro, Richard, Conceição, & Rodrigues, ) and environmental factors (salinity, photoperiod, dissolved oxygen, water current) (Fjelldal et al., ; Hattori et al., ; Kurokawa et al., ; Okamoto et al., ). In the present study, 34.22% of individuals had skeletal abnormalities, which is higher than that documented for other species, such as D. dentex (Koumoundouros, Divanach, & Kentouri, b), P. fulvidraco (Huang et al., ), T. ovatus (Zheng et al., ) and P. erythrinus (Boglione et al., ). This difference might be due to differences in physical variables, species characteristics, environmental factors and culture conditions.…”
Section: Discussioncontrasting
confidence: 61%
“…While the expression of RXRb reached the highest level on 1 DPH and reduced to a low level after first feeding. Like most marine fish larvae, significant structural changes occurred in golden pompano larvae before first feeding (Ma et al 2012Zheng et al 2014). Higher expressions before first feeding observed in the present study may indicate that both RXRa and RXRb are essential during the early development in golden pompano larvae when an intense process of body differentiation occurs (Villeneuve et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although the early ontogenetic development of digestive functionality (Ma et al 2014a, b) and weaning protocols for rearing golden pompano have been studied (Ma et al 2014e), high malformation during early development stage of this species has severely compromised its production efficiency in hatchery. Previous studies have identified the type, position, and frequency of jaw and skeleton malformations in hatchery reared golden pompano larvae (Ma et al 2014d;Zheng et al 2014), but factors causing malformations on this fish remain to be elucidated. The objective of the present study was first to explore the developmental pattern of RXR genes expression in fish larvae from 0 to 5 DPH, and then to evaluate the expression of RXRs during the development of golden pompano larvae in response to dietary treatments in the Artemia nauplii feeding phase.…”
Section: Introductionmentioning
confidence: 99%
“…Fish were anaesthetised by overdosing of Aqui-S (AQUI-S, New Zealand) and fixed in 10% neutral buffered formalin. Jaw deformity was assessed by observing under a stereo microscope (Olympus SZ40, Japan) using the criteria described by Ma et al (2016) and spine and caudal fin deformities were assessed and analysed according to the method described by Zheng et al (2014).…”
Section: Methodsmentioning
confidence: 99%
“…The life cycle of golden pompano has been closed in captivity and several other key aspects, such as food and feeding, development of the larval digestive system and weaning have been successfully explored 2015a,b), Incidence of jaw and skeletal malformation during the early development stages has severely reduced the production efficiency of golden pompano (Ma et al, 2016). Our previous studies have identified the type, position and frequency of jaw and skeletal malformations in hatchery reared golden pompano larvae (Ma et al, 2016;Zheng et al, 2014). Nonetheless, factors causing skeletal malformation are still not clear in this species.…”
Section: Introductionmentioning
confidence: 99%